Rancang Bangun Prototipe Mesin Gravir Laser Berbasis Mikro-kontroler Arduino - Nanang Ali Sutisna; Harist Fauzi (President University, 2019)
Nowaday, the use and demand of laser engraving machines is increasing for production and practical activities in vocational schools and engineering faculty in Indonesia. However, the price of laser engraving machine in the market is still quite high. Therefore, there is a need to find a solution to overcome this problem by designing a laser-engraving machine that is devoted for practical purposes at affordable prices. The control system on the laser-engraving machine is designed using an Arduino Nano-based 2-axis CNC controller, with three stepper motor drive actuators, to drive the machine on the x, y, z axis and laser axis with 2500 mW of power. To prevent damage if there is a movement error, the machine is equipped with emergency stop button. The use of a control system with an Arduino nano-based 2-axis CNC microcontroller is selected on the laser engraving machine because it is open source and more affordable. It is expected that by implementing Arduino nano ATmega328 microcontroller as a prototype, in the future the control system can be developed further so that the control system is more stable. From the results of laser engraving machine testing using laser distance parameters, laser power and laser speed motion, obtained the value of the best engraving machine parameters to be used as standard parameters.